Evidence of a North-South Trend Between AUSGeoid98 and the Australian Height Datum in Southwest Australia - Featherstone, Will (Institution of Engineering and Mining Surveyors Australia Inc., 2004)
The AUSGeoid98 gravimetric geoid model has been compared with 48 GPS-levelling points at a ~50 km spacing across part of the southwest of Western Australia. This is arguably the best subset of GPS-derived ellipsoidal heights in Australia with an internally estimated precision of <±9mm. The sprit-levelled heights were tied to the Australian Height Datum (AHD) using class C techniques [12mm-root-km allowable misclose]. The comparisons show that AUSGeoid98 gives a GPS height transformation to the AHD with a precision of ~±13 cm, which is less than reported earlier (~±36 cm) for a nationwide dataset. A clear north-south trend of ~0.81 mm/km [ppm] is also evident in the differences; of which approximately one-third is attributable to a north-south error in the AHD induced by dominant north-south sea surface topography effects at the nearby fixed tide gauges. After removal of this north-south trend, the standard deviation of the differences reduces to ~5 cm.